Advances in the technology of managing people : contemporary issues in business - Gordon, Pamela Ann; Overbey, Julie A. (Emerald Publishing Limited, 2019)
Advances in the Technology of Managing People: Contemporary Issues in Business presents a wide ranging examination of emerging technological trends in the workplace. Using a combination of research study results, case studies, literature reviews, and conceptual papers, the book examines contemporary issues and emerging trends within management technology.Each chapter focuses on a different technological issue or trend within business management from a variety of perspectives, including management, HR, ethical, and organizational behavior viewpoints. Issues explored in the book include: Workplace Productivity with Balanced Scorecard Actions; Managing Emerging Technology and Organization with Agility; Freelance Economy; E-Mentoring 2.0; Virtual Team Success with the Power of Technology Advancements; Advanced Analytics, Machine Learning and Artificial Intelligence in the Workplace; Ambient Intelligence Changes the Office Environment; Disruptive Innovations and Blockchain; Quantum Leadership. Pamela Ann Gordon and Julie A Overbey curate an excellent reference for research scholars, practitioners, and organizational leaders seeking to understand the impact of technology on contemporary organizations.
Includes index.
Keywords: Industrial management -- Technological innovations.; Leadership.; Business & Economics -- Management.; Business & management.; elektronické knihy; electronic books